2013
DOI: 10.1097/pas.0b013e31826f0447
|View full text |Cite
|
Sign up to set email alerts
|

Nephrogenic Adenoma

Abstract: Nephrogenic adenoma of the urinary bladder, where they present most frequently, are typically confined to the lamina propria but can on occasion focally involve the superficial muscularis propria. Less commonly, nephrogenic adenoma involves the renal pelvis and ureter where again they almost always only involve the lamina propria. We identified 3 consult cases in which tubules of nephrogenic adenoma extensively involved the muscularis propria and focally infiltrated the perinephric adipose tissue, for which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Nephrogenic adenoma can recur after resection and rarely presents with perinephric adipose tissue involvement 13. One of our patients with a history of high-grade invasive urothelial carcinoma developed a classic nephrogenic adenoma followed by recurrent fibromyxoid nephrogenic adenoma.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Nephrogenic adenoma can recur after resection and rarely presents with perinephric adipose tissue involvement 13. One of our patients with a history of high-grade invasive urothelial carcinoma developed a classic nephrogenic adenoma followed by recurrent fibromyxoid nephrogenic adenoma.…”
Section: Discussionmentioning
confidence: 71%
“…Nephrogenic adenoma can recur after resection and rarely presents with perinephric adipose tissue involvement. 13 One of our patients with a history of high-grade invasive urothelial carcinoma developed a classic nephrogenic adenoma followed by recurrent fibromyxoid nephrogenic adenoma. The recurrent fibromyxoid nephrogenic adenoma involved the muscularis propria, which could potentially have been misdiagnosed as muscularis propria invasion by carcinoma, leading to overstaging and possible overtreatment.…”
Section: Discussionmentioning
confidence: 86%
“…However, there are also reports of NA infiltrating deep into the perinephric adipose tissue, which should be paid more attention by pathologists. [6] NA hardly develops into malignant progression and metastasis, but it has been reported that bladder NA could transform into moderately differentiated bladder adenocarcinoma after repeated resection of the lesion. [29] Hartmann et al [7] also reported that a 70-yearold female patient with bladder NA subsequently progressed to clear cell adenocarcinoma after multiple recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…[5] In addition, NA tends to perinephric adipose tissue infiltration and malignant transformation, which needs to be considered by the clinicians. [6,7] Thus, regular followup examinations post-operation are essential for patients with NA. Herein, we report for the first time a 46-year-old male patient presenting with painless gross hematuria, with no predisposing factors of renal pelvis NA, whose diagnosis was confirmed by histopathology and immunohistochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…These findings supported the diagnosis of nephrogenic adenoma. 2
Fig. 3 Pathological examination of an ureteroscopic biopsy revealed an adenoid tubular structure consisting of a single layer of cuboidal epithelium in the lamina propria of the urothelium.
…”
Section: Case Presentationmentioning
confidence: 99%